Private Sector, Small Scale, Grid-connected Renewable Power Generation in Sri Lanka : A Review of the Experience of the Past Decade 1996 to 2006 - World Bank (Washington, DC, 2013)
The objective of this report, therefore, is to provide a comprehensive analysis of the development of the renewable power generation sector in the country over a period of ten years, from 1996 to 2006, as a reference for the design of future policy and market interventions in Sri Lanka and other countries. This analysis aims to assist stakeholders to assess the potential for growth in terms of energy contribution from indigenous renewable resources, private sector investment and rural infrastructure development. The report also serves to reveal the conflicting priorities of stakeholders, which impact the development of indigenous energy resources, and thereby create a platform for constructive debate towards realizing a sustainable and optimal outcome for the country.